2012
DOI: 10.1016/j.phytochem.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

RIKEN tandem mass spectral database (ReSpect) for phytochemicals: A plant-specific MS/MS-based data resource and database

Abstract: The fragment pattern analysis of tandem mass spectrometry (MS/MS) has long been used for the structural characterization of metabolites. The construction of a plant-specific MS/MS data resource and database will enable complex phytochemical structures to be narrowed down to candidate structures. Therefore, a web-based database of MS/MS data pertaining to phytochemicals was developed and named ReSpect (RIKEN tandem mass spectral database). Of the 3595 metabolites in ReSpect, 76% were derived from 163 literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
203
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(204 citation statements)
references
References 37 publications
1
203
0
Order By: Relevance
“…This analysis defines spectral proximity between all MS/MS spectra of a dataset and visualizes them in a spectral network (Watrous et al, 2012). For the molecular annotation we compared the MS/MS spectra to a spectral library including the GNPS community contributed spectral library as well as Massbank, ReSpect, HMDB, and NIST14 (Forsythe and Wishart, 2009;Horai et al, 2010;Sawada et al, 2012;Stein, 2014;Wang et al, 2016). The overall goal of such an analysis is to enable robust, untargeted comparison of multiple samples at the molecular level.…”
Section: Experimental Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis defines spectral proximity between all MS/MS spectra of a dataset and visualizes them in a spectral network (Watrous et al, 2012). For the molecular annotation we compared the MS/MS spectra to a spectral library including the GNPS community contributed spectral library as well as Massbank, ReSpect, HMDB, and NIST14 (Forsythe and Wishart, 2009;Horai et al, 2010;Sawada et al, 2012;Stein, 2014;Wang et al, 2016). The overall goal of such an analysis is to enable robust, untargeted comparison of multiple samples at the molecular level.…”
Section: Experimental Conceptmentioning
confidence: 99%
“…With a medium resolution (R m/z 200 = 17.000), the iterative scan cycles result in several thousand spectra per sample. To reduce redundancy and computation time we clustered identical spectra to consensus spectra (Frank et al, 2008) and searched them against several spectral libraries, including GNPS (Wang et al, 2016), MassBank (Horai et al, 2010), ReSpect (Sawada et al, 2012) HMDB (Forsythe and Wishart, 2009), and NIST 2014 (Stein, 2014). Hereby a strict precursor mass tolerance of m/z 0.01 was used first, followed by a maximum allowed precursor delta mass of up to m/z 100, with the intention to annotate putative analogs.…”
Section: Tandem Mass Spectrometry and Spectral Networkingmentioning
confidence: 99%
See 1 more Smart Citation
“…After selection of a particular m/z ion and Q2 fragmentation, the dependent (Q3) product ion scans were performed between 80 and 1300 m/z. In the ion source ion spray voltage was set at −4500 V, the curtain gas (N 2 ) pressure was set at 40 psi, spray gas (N 2 ) pressure at 30 psi, drying gas (N 2 ) pressure at 30 psi, and ion source temperature at 500 • C. The recorded MS/MS spectra were evaluated using the RIKEN tandem mass spectral database (Sawada et al, 2012), MassBank database (Horai et al, 2010), by scientific data found in the literature and by the use of fragmentation rules (McLafferty and Tureček, 1993). …”
Section: Hplc-ms/ms Identificationmentioning
confidence: 99%
“…erefore, reporting and creating databases of tandem mass spectrum data of rare biological metabolites is important for enriching metabolome annotation data as performed by HMDB and ReSpect (http://spectra.psc.riken.jp/). 28) Although MS/MS spectra-based identi cation of biomarker metabolites and plant secondary metabolites has been reported, [29][30][31][32] structural elucidation of unknown metabolites from MS and MS/MS data is still a di cult task owing to lack of diversity in the measured MS/MS data in the databases and poor methodology for searching the similarity. 33,34) It should be noted that one of the most straightforward ways for certain identi cation of the metabolite structure is still the spectroscopic analysis of isolated metabolites.…”
Section: Bottleneck In the Metabolomics 1: Structural Elucidation Of mentioning
confidence: 99%